2019
DOI: 10.3389/fimmu.2019.01522
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Responses Induced by DNA Vaccines Based on the DENV2 E and NS1 Proteins in Mice: Importance in Protection and Immunodominant Epitope Identification

Abstract: The importance of the cellular immune response against DENV has been increasingly highlighted in the past few years, in particular for vaccine development. We have previously constructed two plasmids, pE1D2, and pcTPANS1, encoding the envelope (E) ectodomain (domains I, II, and III) and the non-structural 1 (NS1) protein of dengue virus serotype 2 (DENV2), respectively. In the present work, we analyzed the induction of the cellular response in mice immunized with these DNA vaccines and identified the immunogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…Among reported dengue vaccine studies, E protein is regarded as the major target antigen with multiple neutralizing antibody sites, while the NS1 protein, which has no neutralizing antibody sites, is often neglected. However, some experimental studies have shown that ZIKV and DENV prototype NS1 vaccines can prevent the development of lethal infections in experimental conditions, 20 , 46 , 47 possibly due to FcR-mediated complement activation or antibody-dependent, cell-mediated cytotoxicity (ADCC) induced by NS1-specific antibodies elicited by NS1 protein vaccines. 48 , 49 We observed that E80-mRNA+NS1-mRNA elicited a lower titer of NS1-specific antibody than NS1-mRNA did, probably due to antigenic competition between E80 and NS1 proteins, as reported in some studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among reported dengue vaccine studies, E protein is regarded as the major target antigen with multiple neutralizing antibody sites, while the NS1 protein, which has no neutralizing antibody sites, is often neglected. However, some experimental studies have shown that ZIKV and DENV prototype NS1 vaccines can prevent the development of lethal infections in experimental conditions, 20 , 46 , 47 possibly due to FcR-mediated complement activation or antibody-dependent, cell-mediated cytotoxicity (ADCC) induced by NS1-specific antibodies elicited by NS1 protein vaccines. 48 , 49 We observed that E80-mRNA+NS1-mRNA elicited a lower titer of NS1-specific antibody than NS1-mRNA did, probably due to antigenic competition between E80 and NS1 proteins, as reported in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many vaccine candidates having been tested, 11 , 12 , 17 , 18 , 19 , 20 , 21 CYD-TDV (Dengvaxia) of Sanofi Pasteur is the only licensed dengue vaccine that provides protection for people who have already been infected with DENV; however, the vaccine appears to have increased the incidence of severe dengue disease in those who were naive to DENV infection. 22 This has been observed in the Philippines, where 19 children who had been vaccinated with Dengvaxia died of a subsequent DENV infection.…”
Section: Introductionmentioning
confidence: 99%
“…A HIV-1 DNA vaccine DNA-4, which encodes the Pol(rt), gp140, Nef, and Gag proteins of HIV-1, was found to be safe, well-tolerated and capable to induce robust immune responses [ 156 ]. DNA vaccines from the envelope (E), ectodomain (domains I, II, and III), and the non-structural 1 (NS1) protein of dengue virus serotype 2 (DENV2) protected against lethal DENV2 challenges [ 157 ]. A DNA vaccine encoding the SARS-CoV S-protein induced T cell and neutralizing antibody responses in animals [ 158 ].…”
Section: Overview: Pathways Towards An Effective Covid-19 Vaccinementioning
confidence: 99%
“… Dengue BALB/c and C57BL/6 mice (in-vivo model) Plasmids containing ns1 gene (pcTPANS1) and ectodomain of E protein (pE1D2) T-cell epitopes Intramuscular (IM); 2 14 50 μg in 50 μL PBS ELISPOT (measurement of INF-gamma and identification of positive peptides) + Cytokine staining (TNF-alfa and INF-gamma production) For BALB/c mice, 95% of survival rate in immunized mice with pE1D2, 85% in mice immunized with pcTPANS1 vs 30% of survival rate in mice immunized with plasmid control vector pCTPA and 20% of non-immunized mice. [ 27 ] HLA-A2 transgenic mice (in-vivo model) 6 HLA-A2 + , A2 + /A24 + dual binding Dengue virus peptides formulated in calcium phosphate nanoparticles (individually or as pools) T-cell epitopes Not specified; 3 7 10 µg pooled free peptides with ISA51 (10 µg of each peptide/150 µL); 50 µg pooled free peptides with ISA51 (50 µg of each peptide/150 µL); 10 µg of particle/multipeptide formulation (10 µg of each peptide/150 µg with nanoparticle); 50 µg of particle/multipeptide formulation (50 µg of each peptide/150 µL with nanoparticle) N-acetylglucosamine and Montanide ISA51 ELISPOT (measurement of INF-gamma) Peptides formulated with nanoparticles were seen to induce a strong CD8 + T-cell response. The lower concentration of nanoparticles/multipeptide formulation generated the highest T-cell responses.…”
Section: Next Generation Vaccinology For Ntdsmentioning
confidence: 99%